Review of Tobacco Taxes Advocacy in Indonesia: A Health Promotion Strategies - Pambudi, Tesalonika Arina; Randa Arnika Murtiningtyas (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2024)
Background: The global smoking prevalence from 2007 to 2021 decreased from 22.7% to 17%.  However, in some countries, the prevalence has not changed or even increased.  Indonesia is the third largest country in cigarette consumption. Data shows about 58 million male smokers and 3.5 million female smokers smoke every day.  Many tobacco control efforts have been made, including efforts to increase cigarette excise taxes. In the process, there are advocacy efforts included in the health promotion strategy according to WHO in the Ottawa Charter. However, a complete review of the process and results of advocacy is still lacking, even though it can be used to evaluate the implementation of advocacy for future excise tax increases. Aims: This research aims to review the process and results of advocacy as a health promotion strategy in tobacco control. Methods: This research involves CISDI (Center for Indonesia’s Strategic Development Initiatives). The method used was Focus Group Discussion with CISDI and secondary data from political mapping in assessing advocacy results. Results: Advocacy of the excise tax increase policy carried out by CISDI received support from officials or the public amounting to 70.2% and only 23.6% disagreed. Conclusion: Health promotion strategies through advocacy can increase awareness and support from policy makers quite effectively. Tobacco control through increasing tobacco taxes can be carried out if all parties encourage the government to make policies. However, in reality, an increase in tobacco taxes alone cannot reduce cigarette consumption in the community.